DIAGNOSIS AND TREATMENT OF MALIGNANT EPITHELIAL SKIN TUMORS (PROJECT) (Опухоли головы и шеи)
Objective and status of the guidelines. These Clinical guidelines consolidate opinions of the members of the expert task group on current problems of diagnosis and treatment of skin cancer at the modern stage of Russian clinical practice. The guidelines embody experience in diagnosis and treatment of this pathology of the leading specialists of scientific research institutes and large oncological centers of the Russian Federation. The guidelines were composed considering operation of oncological dispensaries with different bed capacities and diagnostic capabilities, and therefore opinions of some members of the group can differ from the version presented below. At the same time, the proposed for discussion guidelines make no claim to fully represent all aspects of the problem and can’t replace guidelines for doctors, textbooks, and scientific papers in this field.The main objective of the guidelines is to improve early diagnosis of malignant skin pathology, its treatment, functional and social rehabilitation of patients with this pathology.The Guidelines are based on analysis of the current state of diagnosis and treatment of malignant skin tumors of the head and neck considering experience of the leading specialists in the field and reports presented at the task group meeting on February 17th, 2017 in Kazan.